Short & shivery thirty chilling tales - San Souci, Robert D. (Doubleday & Co, 1987)
A collection of thirty short and spooky tales from the folklore of Russia, Virginia, Ireland, Canada, and other areas of the world
Keywords: Ghost stories; Tales